Decline in adolescent drinking: Some possible explanations. (19th July 2020) - Rossow, Ingeborg; Pape, Hilde; Torgersen, Leila
Abstract: Introduction and Aims: Adolescent drinking has decreased in numerous high‐income countries in the 2000s, and how to explain this downward trend is far from clear. Focussing on the decline in drinking to intoxication among youth in Norway, we examined the following potential explanatory factors: family/home‐based and peer‐oriented leisure‐time activities, perceived parental drinking, drug substitution, school conscientiousness and delinquency. Design and Methods: Data stemmed from cross‐sectional surveys of adolescents aged 13–17 years in the four largest cities in Norway in 2002 ( n = 1204) and in 2013/2015 ( n = 31 441). We examined the extent to which the decline in intoxication prevalence was attributable to the possible explanatory variables using logistic regression analysis. Results: The proportion reporting any past‐year intoxication episodes dropped markedly from 2002 (41%) to 2013/2015 (22%). Family/home‐oriented leisure‐time activities and school conscientiousness increased, whereas hanging out with friends in the evening and delinquent behaviours decreased. These factors together accounted for 43% of this decline. Decrease in going out with friends was the most important factor. We found no empirical support for assumptions that perceived parental drinking or drug substitution had contributed to the decrease in drinking to intoxication. Discussion and Conclusions: Since the millennium shift, urban adolescents in Norway have become more home‐, family‐ and school‐oriented, and less involved in unsupervised socialising with peers and delinquency. These changes may have contributed to some of the reduction in the prevalence of intoxication in this population group.